3R Training as an Educational Tool to Change Perceptions and Attitudes Towards Waste Management - Aisyah Sisilia Pratyaningrum; Arni Dwi Yuni Astuti; Rona Muna Azizi; Safna Fathin Al-Zuhroh; Muchamad Ifan Maulana; Apriliana Drastisianti (Universitas Palangka Raya, 2024)
The waste management training in Johorejo Village aims to increase public awareness and knowledge, especially PKK women to know about the importance of waste management based on the 3R (Reduce, Reuse, Recycle) principle. The type of research used is a descriptive qualitative approach with data collection through interviews and observations. The subjects of this study are all Johorejo residents. This activity includes the delivery of materials, mentoring, and evaluation. The material presented included waste management, 3R principles, identification of types of waste, and the dangers of indiscriminate waste disposal. The results of the training showed an increase in participants' understanding of waste hazards and a change in attitudes that are more concerned about the environment. Participants began to practice the 3R principles and plan further activities such as the creation of a waste bank and a recycling program in the village. The training proved to be effective in raising environmental awareness among participants, with relevant and practical methods, so that they were better prepared to manage waste responsibly.